2021
DOI: 10.1016/j.gca.2021.02.032
|View full text |Cite
|
Sign up to set email alerts
|

The Mg isotope signature of marine Mg-evaporites

Abstract: Marine Mg-evaporites are a small oceanic sink of magnesium, precipitating only from extremely evaporated brines. The isotopic composition of Mg in seawater, d 26 Mg seawater , has recently been shown to be an effective tool for reconstructing the Mg budget of the modern and past oceans. However, estimations of the Mg isotope fractionation between the Mg-evaporites and their precipitating solution are required for full quantification of the isotope effect of the evaporitic sink on d 26 Mg seawater , as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Recent studies on the Mg isotope fractionation during precipitation of clay minerals and salts have shown that the magnitude and direction of isotope fractionation depends on the Mg‐O bond length and the amount of water molecules that have to be dehydrated during the formation of the minerals, and that the magnitude of isotope fractionation, consistent with equilibrium fractionation, decreases with increasing temperatures (Hindshaw et al., 2020; Li et al., 2014; Shalev et al., 2021). In addition, pH values may also have an influence on the magnitude of Mg isotope fractionation, which has been explained by differences in octahedral bond length (Shalev et al., 2021). To study the isotopic fractionation during the precipitation of caminite and thus calculate potential caminite compositions in the volcanic basement at Lower Cone, we have chosen an experimental setup that is similar to natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the Mg isotope fractionation during precipitation of clay minerals and salts have shown that the magnitude and direction of isotope fractionation depends on the Mg‐O bond length and the amount of water molecules that have to be dehydrated during the formation of the minerals, and that the magnitude of isotope fractionation, consistent with equilibrium fractionation, decreases with increasing temperatures (Hindshaw et al., 2020; Li et al., 2014; Shalev et al., 2021). In addition, pH values may also have an influence on the magnitude of Mg isotope fractionation, which has been explained by differences in octahedral bond length (Shalev et al., 2021). To study the isotopic fractionation during the precipitation of caminite and thus calculate potential caminite compositions in the volcanic basement at Lower Cone, we have chosen an experimental setup that is similar to natural conditions.…”
Section: Discussionmentioning
confidence: 99%
“…However, authigenic clay minerals usually form in saline and alkaline lake systems. In saline and alkaline lakes, authigenic minerals, such as Mg-rich clay minerals and Mg-rich evaporites, will compete for Mg 2+ with dolomite [79,80]. In non-alkaline saline lakes, authigenic Mg minerals like Mg-rich clay and Mg-rich evaporites either precipitate to a minimal extent or do not deposit [21].…”
Section: Numerical Model Of Magnesium Cycling and Isotopic Mass Balan...mentioning
confidence: 99%
“…and non-traditional metal isotopes (Ca, Mg, Mo, etc. ), provide novel approach in determining the effects of BSR/TSR (e.g., Cai et al, 2017), thermal histories (e.g., Mangenot et al, 2018;Cong et al, 2021), organic matter enrichment mechanisms (e.g., Zhu et al, 2022), diagenetic fluid properties (e.g., Shalev et al, 2021;Bryant et al, 2022).…”
Section: Prospectsmentioning
confidence: 99%